The literary and cultural reception of Charles Darwin in Europe - Glick, Thomas F.,Shaffer, E. S. (Bloomsbury, 2014)
Beyond this pivotal place in the history of scientific thought, Charles Darwin's writings and his theory of evolution by natural selection have also had a profound impact on art and culture and continue to do so to this day. This book is a comprehensive survey of this enduring cultural impact throughout the continent. With chapters written by leading international scholars that explore how literary writers and popular culture responded to Darwin's thought, the book also includes a complete timeline of his cultural reception in Europe and bibliographies of major translations in each country
Erschienen: 3 - 4
Keywords: Aufsatzsammlung